Efektifitas Media Kahoot dalam Pembelajaran PPKn untuk Meningkatkan Penalaran Kritis Peserta Didik Sekolah Dasar Kecamatan Tamansari - Anuraga, Bayu Septian; Dwijayanti, Ida; Sumarno, Sumarno (AS-SABIQUN, 2024)
Mastery of information technology has become the "lifestyle" of most people, especially the younger generation. Along with the shift of the world order from the traditional realm to the digital realm, the development of information and communication technology has also penetrated into the field of education. This study aims to determine that kahoot media can improve students' critical reasoning on PPKn learning in elementary school teachers, Tamansari District, Boyolali Regency. The research method uses a qualitative approach based on the philosophy of postpositivism. The population survey of this study was 12 teachers and 34 students consisting of 8 schools, and interviews of elementary school teachers. The results prove that kahoot media learning using methods, presentations and practicums is highly favored by teachers, on the one hand different in portraying online learning. Being enthusiastic and challenged, in the end these teachers will apply in their respective schools. This proves that kahoot media can improve students' critical reasoning in PPKn learning with a percentage of 37% very good and 62% choosing good. However, the infrastructure at the training site needs to be improved and improved to support the online learning process like this.